(untitled) (Research, Society and Development, 2023)
Non-carious cervical lesions (NCCL) are common situations in the daily lives of dentists. NCCL are characterized by a process of deformation and/or tooth wear in the cervical region. They are described by the degradation of dental tissues without the influence of carious lesions. Its etiology is associated with some chronic risk factors. Among the characteristics of clinical presentation, NCCL can vary from shallow to deep depressions, with the shape of large discs or conical, its surface can be flat, smooth, shiny or inclined. These injuries can bring as a consequence the difficulty of cleaning, among other evils that will be addressed. This work aimed to deepen knowledge about the etiologies and possible treatments of NCCL, reporting the information obtained through the integrative literature review. Methodology: searches were carried out in the SciELO database; Pubmed; Academic Google; Journal of Oral Rehabilitation; Capes and Bireme periodicals; covering 2016 to 2023. Conclusion: It is necessary to know about the etiological factors of NCCL, since the same factors will influence its clinical presentation and treatment. Wedge-shaped lesions are more likely to progress in depth, interfering with the vitality, aesthetics, function and structure of the tooth. Therefore, one must know how to intervene at the right time. New research should be carried out in order to better understand its etiological factors, its correlation with oral microorganisms and its indications and possibility of treatment.